DETEKSI PENYAKIT MOTILE AEROMONAS SEPTICEMIA PADA IKAN PATIN SIAM (PANGASIUS HYPOPHTHALMUS) MENGGUNAKAN METODE ELISA - Maulina, Herlina (Jurnal Mina Sains, 2015)
This study was conducted to determine the prevalence of Motile Aeromonas Septicemia of Siamese catfish farming at Cibeureum Subdistrict, Ciseeng Subdistrict, Kemang Subdistrict, and Parung Subdistrict (in Bogor Region) using antigen supernatant with concentration of RAC 1:200 and antigen pellet with concentration of RAC 1:5,000. Samples of serum obtained from 10 Siamese catfish per district have weight 300-400 g/fish. The collection of serum as much 1-4 mL obtained from 3-5 mL of blood per fish. Collection of serum which had been collected from each district then was tested using indirect ELISA method. The indirect ELISA method use the two types of dilution of serum RAC (Rabbit Anti-Catfish) and two types of antigens, i.e dilution of RAC 1:200 with antigen supernatant (group A) and dilution of RAC 1:5000 with antigen pellet (group B). Determination of the sample area exposed to positive or negative MAS disease was known of cut-off values that has been defined as a comparison, the results of the test sample with a value of OD (Optical Density) â¤ 0.011; 0,015; 0.006; 0.004; 0.000; 0.005 showed positive of MAS attacked and value of OD â¥ 0.017; 0.025; 0.018; 0.016; 0.016; 0.014 showed negative of MAS attacked. The results of research showed the prevalence 60-100% on RAC 1:5,000 dilution with antigen pellet, and the prevalence 20-60 % on RAC 1:200 dilution with antigen supernatant